Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Why is the following implication true?

$${d\over dt}\vec v(t)=\vec n\times \vec v(t) \implies \vec n\cdot\vec v(t)=\vec n\cdot \vec v(0)$$

I think the result can be obtained by expressing $\vec v(t)$ in a Taylor series expansion in $t$. And from $\displaystyle {d\over dt}\vec v(t)=\vec n\times \vec v(t) $, we see that $\vec n\cdot \vec v^{(n)}(0)=0$ due to the $\times \vec n$ bit.

Is there a more direct way?

share|improve this question

1 Answer 1

up vote 1 down vote accepted

$$ \vec n\cdot\frac{d\vec v(t)}{dt}=\vec n\cdot(\vec n\times \vec v(t))=0 $$ then $$ \frac{d}{dt} \vec n\cdot\vec v(t)=0 $$ that means $\vec n\cdot\vec v(t)=constant$. The constant can be fixed through $\vec v(0)$ and you are done.

share|improve this answer
    
Thank you, Jon! –  Matthew 1629 Dec 9 '12 at 16:09

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.